PENDALAMAN DAN PENGEMBANGAN MATERI PAI KELAS X MADRASAH ALIYAH BIDANG AL-QUR’AN HADIS - Rainatul Agustina, Nadya; Fadhli Rabbi, Mim; Barni, Mahyuddin (Berajah Journal, 2024)
This study aims to explore and develop Islamic Religious Education (PAI) materials in the field of Al-Qur'an and Hadith at the Madrasah Aliyah level. The background of this research is the importance of a deep understanding and development of teaching materials to suit the times and the needs of students. The research method used was descriptive qualitative with a case study approach in several Madrasah Aliyah. Data were obtained through observation, interviews, and documentation studies. The results showed that there are several aspects of Al-Qur'an and Hadith materials that require further deepening, such as the historical context of verses and hadith, relevance to contemporary issues, and the application of the values contained in everyday life. In addition, material development also involves the use of more varied and interactive learning methods, including the use of information and communication technology (ICT) to increase the attractiveness and effectiveness of learning. This finding is expected to be a reference for PAI teachers in developing more effective curriculum and learning strategies. With the proper deepening and development of materials, it is expected that students can better master the knowledge of the Qur'an and Hadith, and be able to apply it in their lives.